Pendampingan Penanaman Apotek Hidup Sebagai Upaya Pemenuhan Kebutuhan Keluarga di Masa Pandemi Covid-19 - Aesthetica Islamy; Wiwid Yuliastuti; Qurrotu A’Yunin Lathifah (Jurnal SOLMA, 2021)
Planting a live pharmacy is very important for the community, especially to increase the body's source of immunity during the Covid-19 pandemic. This service aims to provide knowledge to the community, especially mothers in Tapan Village, Kedungwaru District, Tulungagung Regency, East Java Province regarding the importance of living pharmacies. The method of implementing community service activities is offline and online assistance. Mentoring participants were representatives of cadres from Tapan Village, Kedungwaru District, Tulungagung Regency. In order to see the added value and usefulness of service activities, before and after service activities, participants will be asked to fill out a questionnaire made with Google Form. The results of the assessment of the usefulness of service activities with the results of 27% very useful and 73% useful. This service activity can run smoothly. Based on the activities carried out by the service team, it can be concluded that there was an increase in participants' knowledge about the importance of the benefits of living pharmacies as a means of meeting family needs for cost-effective and chemical-free medicines in the Covid-19 pandemic era.